Medial Parietal Cortex Activation Related to Attention Control Involving Alcohol Cues - Gladwin, Thomas E.; ter Mors – Schulte, Mieke H.; Ridderinkhof, K Richard; Wiers, Reinout W. (Frontiers in Psychiatry, 2013)
Automatic attentional engagement toward and disengagement from alcohol cues play a role in alcohol use and dependence. In the current study, social drinkers performed a spatial cueing task designed to evoke conflict between such automatic processes and task instructions, a potentially important task feature from the perspective of recent dual-process models of addiction. Subjects received instructions either to direct their attention toward pictures of alcoholic beverages, and away from non-alcohol beverages; or to direct their attention toward pictures of non-alcoholic beverages, and away from alcohol beverages. Instructions were varied per block. Activation in medial parietal cortex was found during “approach alcohol” versus “avoid-alcohol” blocks. This region is associated with the, possibly automatic, shifting of attention between stimulus features. Subjects thus appeared to shift attention away from certain features of alcoholic cues when attention had to be directed toward their location. Further, activation in voxels located close to this region was negatively correlated with riskier drinking behavior. A tentative interpretation of the results is that risky drinking may be associated with a reduced automatic tendency to shift attention away from potentially distracting task-irrelevant alcohol cues. Future study is needed to test this interpretation, and to further determine the role of medial posterior regions in automatic alcohol-related attentional processes in general.